Estimation of pitch angle diffusion rates and precipitation time scales of electrons due to EMIC waves in a realistic field model. Issue 10 (24th October 2015) - Kang, Suk‐Bin; Min, Kyoung‐Wook; Fok, Mei‐Ching; Hwang, Junga; Choi, Cheong‐Rim
Abstract: Electromagnetic ion cyclotron (EMIC) waves are closely related to precipitating loss of relativistic electrons in the radiation belts, and thereby, a model of the radiation belts requires inclusion of the pitch angle diffusion caused by EMIC waves. We estimated the pitch angle diffusion rates and the corresponding precipitation time scales caused by H and He band EMIC waves using the Tsyganenko 04 (T04) magnetic field model at their probable regions in terms of geomagnetic conditions. The results correspond to enhanced pitch angle diffusion rates and reduced precipitation time scales compared to those based on the dipole model, up to several orders of magnitude for storm times. While both the plasma density and the magnetic field strength varied in these calculations, the reduction of the magnetic field strength predicted by the T04 model was found to be the main cause of the enhanced diffusion rates relative to those with the dipole model for the same Li values, where Li is defined from the ionospheric foot points of the field lines. We note that the bounce‐averaged diffusion rates were roughly proportional to the inversion of the equatorial magnetic field strength and thus suggest that scaling the diffusion rates with the magnetic field strength provides a good approximation to account for the effect of the realistic field model in the EMIC wave‐pitch angle diffusion modeling. Key Points: Diffusion rates and precipitation time scales due to EMIC waves are calculated using the T04 model The rates increase by up to several orders of magnitude compared to those based on the dipole model The enhancement in the rates is mainly due to a decrease in the magnetic field strength